Social economic risk analysis of Lithuania in the context of European Union countries - Jurgelevičius, Artūras (Buhalterinės apskaitos teorija ir praktika, 2014)
Social economic risk factors of country risk assessment of Lithuania have been analysed in the article.  Recent economic downturn caused and sharpened a number of economic and social problems. Poor economic recovery, high rate of unemployment, social and economic inequality, not flexible and dynamic structure of industry might be considered as factors which will limit the economic growth and prosperity in the country for upcoming decade. Analysis has suggested that Lithuania has reached 72% of European Union economic level. In order to achieve the average of European Union’s countries economic level Lithuania has to gain more than 4% of growth of GDP rate annually. In the context of regional deep recession or country’s dependency on European market, it seems impossible to achieve this goal in 2030 if other variables have not change.  Analysis of Lithuanian industry and export structure suggested that Lithuania mainly produce low value added goods and this has not changed for the last decade. It was identified that Lithuania is experiencing high level of social exclusion which negatively affect the development of the country. Social economic trends might do high pressure on state budget demanding increase taxes tariffs and expand tax base in the country.
Keywords: Lithuania's social economic risk; economic growth